2012
DOI: 10.2105/ajph.2011.300621
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Implicit Bias on Treatment Recommendations for 4 Common Pediatric Conditions: Pain, Urinary Tract Infection, Attention Deficit Hyperactivity Disorder, and Asthma

Abstract: Pediatricians' implicit attitudes about race affect pain management. There is a need to better understand the influence of physicians' unconscious beliefs about race on pain and other areas of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
333
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(360 citation statements)
references
References 43 publications
12
333
7
Order By: Relevance
“…Green and colleagues 45 found that resident clinicians with greater implicit bias were less likely to recommend thrombolytic therapy for a hypothetical black patient with myocardial infarction, but this did not occur when the patient was described as white. On the other hand, research on pediatric decision making 49,50 showed that some hypothetical decisions were associated with implicit bias but others were not. However, a study 51 with medical students failed to find any relation between clinical decisions in the hypothetical scenarios and the students' implicit bias.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
“…Green and colleagues 45 found that resident clinicians with greater implicit bias were less likely to recommend thrombolytic therapy for a hypothetical black patient with myocardial infarction, but this did not occur when the patient was described as white. On the other hand, research on pediatric decision making 49,50 showed that some hypothetical decisions were associated with implicit bias but others were not. However, a study 51 with medical students failed to find any relation between clinical decisions in the hypothetical scenarios and the students' implicit bias.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
“…39 The Implicit Association Test is an indirect measure of implicit social cognition or prejudice, including among clinicians. [49][50][51][52] It is a computer-based reaction measure of the relative strength between positive and negative associations toward one social group compared with another. Clinician implicit bias has been associated with physician treatment recommendations and patient-rated quality of medical visit communication and care.…”
Section: Racial and Other Forms Of Discriminationmentioning
confidence: 99%
“…Clinician implicit bias has been associated with physician treatment recommendations and patient-rated quality of medical visit communication and care. 51,52 Such a tool may be useful to researchers studying mechanisms through which discrimination and stress affect health throughout the life span.…”
Section: Racial and Other Forms Of Discriminationmentioning
confidence: 99%
“…The study of unconscious cognition has grown in importance and more and more fields became interested in its many facets, such as knowledge management (e.g., Bennet & Bennet, 2008), education (e.g., ECU, 2013;Sun, Mathews, & Lane, 2007), medical care (e.g., Sabin & Greenwald, 2012), consumer behavior (e.g., Dijksterhuis et al, 2005), the law (e.g., Casey et al, 2012), artificial intelligence (e.g., Schank, 2009), and even finance (e.g., Taffler & Tuckett, 2010). However, it has also become more complex, namely with respect to dissociation, of which there is today a plethora of paradigms.…”
Section: Introductionmentioning
confidence: 99%